Therapeutic Dilemma: Prognostic Factors and Outcome for Neuroendocrine Tumors of the Cervix. Issue 3 (1st March 2016) - Abdallah, Reem; Bush, Stephen H.; Chon, Hye Sook; Apte, Sachin M.; Wenham, Robert M.; Shahzad, Mian M.K.
Abstract : Objectives: The aim of this study was to review treatment and outcomes for neuroendocrine tumors (NETs) of the cervix at a National Cancer Institute–designated Comprehensive Cancer Center. Materials and Methods: Data for women with NET of the cervix treated at our institution, since 1999, were collected. Progression-free survival (PFS) and overall survival (OS) were assessed with respect to age, tumor size, tobacco use, lymph node status, stage of disease, and type of treatment. Results: Among 18 patients (median age, 44 years), 9 (50%) had tumors larger than 5 cm and advanced-stage disease (IB2-IV). Seven recurrences were noted (39%). Median PFS was not reached, and median OS was 72.2 months. Surgery was the only factor significantly associated with both PFS and OS (3-year PFS, 90% vs 30%, P = 0.01; 3-year OS: 89% vs 18%, P = 0.019). Age 40 years or younger and absence of lymph node metastases correlated significantly with PFS, with a trend toward improved OS. Recurrences were less likely with stage IA to IB1 compared with stages IB2 to IVA and IVB (hazards ratio, 0.33; P = 0.054), with median OS of 72.2, 19.2, and 7.4 months, respectively ( P = 0.002). Although patients with tumors 4 cm or smaller had better outcomes, this factor did not reach statistical significance. Chemotherapy, radiation therapy, and tobacco use were not associated with survival. Conclusions: Neuroendocrine tumors of the cervix present at a relatively young age, with bulky tumors and advanced-stage disease. Surgery, younger age, smaller tumor size, early stage, and absence of lymph node involvement seem to be associated with improved survival. Nonetheless, optimal management is yet to be determined, and multimodality treatment is advocated.